Young Children Playing Relational Approaches to Emotional Learning in Early Childhood Settings - Alcock, Sophie Jane (International Perspectives on Early Childhood Education and Development, 2016)
The subject of this book is young children's emotional-social learning and development within early childhood care and education settings in Aotearoa-New Zealand. The focus on emotional complexity fills a gap in early childhood care and education research where young children are frequently framed narrowly as 'learners,' ignoring the importance of emotional functioning and the feelings with which children make sense of themselves and the world. This book draws on original data in the form of narrative-like framed events to creatively illustrate the complexities in children's diverse ways of feeling, thinking, playing, being, and becoming. Events illuminate the feelings and meanings of observed experiences in holistic and contextualised gestalts. Awareness of unconscious processes, the feeling of feelings, and cultural dimensions of development and meaning-making are addressed. The book emphasises the emergent and psychodynamic nature of children's development and learning with strong links to the role of play and playfulness in the events, drawing on two ethnographically inspired research projects that present theory, experience and practice in real-life events. .